2019
DOI: 10.3892/mmr.2019.10652
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑195 inhibits epithelial‑mesenchymal transition by targeting G protein‑coupled estrogen receptor 1 in endometrial carcinoma

Abstract: Epithelial-mesenchymal transition (EMT) has been shown to exert promoting effects on the progression of a number of cancer types, including endometrial carcinoma (EC). MicroRNA (miRNA or miR)-195 has been shown to function as a tumor suppressor. This study aimed to explore the potential role of miR-195 in the EMT process of EC. miR-195 overexpression (Mimics) and mimics control (Mock) vectors were constructed and transfected into human endometrial cancer cells (AN3-CA and Hec1A) using Lipofectamine 2000, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…It has also been described that E2, G-1, OHT, IGF-1, and insulin favor the increased expression of GPER at mRNA and protein levels (35,(40)(41)(42). Several studies have reported that direct stimulation with E2, G-1, and OHT increases the carcinogenic characteristics of EC cell lines, such as proliferation, migration, and invasion, involving mechanisms such as activation of signaling pathways like MAPK and PI3K, calcium influx via Cav1.3 and DAKα, phosphorylation of FAK, and increased production of MMP-2/9, c-Fos, and cyclin D1 (33,35,40,41,(43)(44)(45)(46)(47)(48)(49)(50). However, only one report showed the inhibition of proliferation in RL95-2 and HEC-1A cell lines stimulated with G-1 in a dose-dependent manner (37).…”
Section: Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been described that E2, G-1, OHT, IGF-1, and insulin favor the increased expression of GPER at mRNA and protein levels (35,(40)(41)(42). Several studies have reported that direct stimulation with E2, G-1, and OHT increases the carcinogenic characteristics of EC cell lines, such as proliferation, migration, and invasion, involving mechanisms such as activation of signaling pathways like MAPK and PI3K, calcium influx via Cav1.3 and DAKα, phosphorylation of FAK, and increased production of MMP-2/9, c-Fos, and cyclin D1 (33,35,40,41,(43)(44)(45)(46)(47)(48)(49)(50). However, only one report showed the inhibition of proliferation in RL95-2 and HEC-1A cell lines stimulated with G-1 in a dose-dependent manner (37).…”
Section: Endometrial Cancermentioning
confidence: 99%
“…However, only one report showed the inhibition of proliferation in RL95-2 and HEC-1A cell lines stimulated with G-1 in a dose-dependent manner ( 37 ). Also, miR-195 controls GPER expression in vitro in AN3-CA and HEC-1A cells ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review identified 105 original articles and two literature reviews reporting the expression pattern of miRNAs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
“…27 Moreover, miR-195 could suppress the progression of prostate cancer, lung adenocarcinoma and endometrial carcinoma. [28][29][30] A study reported that LINC00355 can sponge miR-195, which inhibits apoptosis promotes the progression of head and neck squamous cell carcinoma. 31 Wu et al demonstrated that BRAF-activated noncoding RNA promotes tumorigenesis of pancreatic cancer by sponging miR-195.…”
Section: Discussionmentioning
confidence: 99%